2004
DOI: 10.1189/jlb.0404259
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of NFAT (nuclear factors of activated T cells) in human CD34+ cells: down-regulation upon myeloid differentiation

Abstract: The calcineurin-dependent, cyclosporin A (CsA)-sensitive transcription factor nuclear factor of activated T cells (NFAT) represents a group of proteins, which is well-characterized as a central regulatory element of cytokine expression in activated T cells. In contrast, little is known about the expression or function of NFAT family members in myeloid cells; moreover, it is unclear whether they are expressed by hematopoietic stem/progenitor cells. Here, we show that NFATc2 (NFAT1) is expressed at high levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 61 publications
2
47
0
2
Order By: Relevance
“…This is most likely due to a mild inability of the AV-NFAT1-expressing cell populations to compete with cells in which the hyperactivable protein is not expressed. These findings are consistent with a previous report showing that as hematopoietic stem cells begin to differentiate, expression of all NFAT family members is downregulated (38,39); in contrast, hyperactivable NFAT1 proteins expressed from the R26 locus would not be downregulated, and progenitor cells expressing these proteins, even at low levels, would display inappropriately sustained NFAT activity, potentially conferring a competitive disadvantage on those cell populations. NFAT1 has been shown to repress expression of the G 0 /G 1 checkpoint kinase cyclin-dependent kinase 4 (CDK4) (40).…”
Section: Discussionsupporting
confidence: 81%
“…This is most likely due to a mild inability of the AV-NFAT1-expressing cell populations to compete with cells in which the hyperactivable protein is not expressed. These findings are consistent with a previous report showing that as hematopoietic stem cells begin to differentiate, expression of all NFAT family members is downregulated (38,39); in contrast, hyperactivable NFAT1 proteins expressed from the R26 locus would not be downregulated, and progenitor cells expressing these proteins, even at low levels, would display inappropriately sustained NFAT activity, potentially conferring a competitive disadvantage on those cell populations. NFAT1 has been shown to repress expression of the G 0 /G 1 checkpoint kinase cyclin-dependent kinase 4 (CDK4) (40).…”
Section: Discussionsupporting
confidence: 81%
“…Our previous studies showed that members of the NFAT family are expressed in hematopoietic progenitor cells and are regulated during myeloid commitment in a lineage-specific manner. 15,16 These results prompted us to investigate the role of NFATc2 in hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, NFATc2 is expressed by both hematopoietic stem cells and stromal cells. 15,26,27 and thus both direct and indirect mechanisms have to be considered as causes for the hematopoietic insufficiency in the bone marrow of NFATc2-deficient animals. Our results suggest that NFATc2 is neither directly nor indirectly involved in the myeloid differentiation of hematopoietic progenitor cells, as the capacity for erythroid and granulocytic differentiation of these cells was maintained in the absence of NFATc2, both within the local bone marrow environment and in extramedullary organs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations